Language motivation and attitudes: a study with English for Academic Purposes learners - Flavia Azeredo Cerqueira (Horizontes, 2015)
Abstract The study investigates English for Academic Purposes (EAP) course learners’ motivation within the L2 Motivational Self System Framework (cf. DÖRNYEI; CLÉMENT, 2001; DÖRNYEI, 2005; CSIZÉR; DÖRNYEI, 2005b) and their achievement. The framework consists of three components, of which the ideal L2 self is the most important in the maintenance of motivation.  Brazilian learners of EAP, students of a federal university in Belo Horizonte, participated in the study. The data was collected by means of questionnaires about attitude and motivation towards the L2, L2 learning and EAP, and also the ethnicity and socioeconomic backgrounds of learners. The EAP course as a program component of a broader, federal Brazilian policy with both national and international stakeholders was also examined. The results suggest that the learners possess a well-established ideal L2 self.  The variables measured in this project presented a positive tendency towards L2 motivation. This confirms that the participants were motivated to learn the L2 language, in this case English.  The socioeconomic and ethnic variables indicate that whites from a middle-class background are the majority group on campus. Recommendations for further research in L2 motivation and policy studies conclude the paper.